HIV-1 Drug Resistance Profiles for the HIV Protease and Reverse Transcriptase Gene in Patients Receiving Combination Therapy in Tehran, Iran - Sadeghi, Leila; Lolaie, Masoomeh; Tabatabai, Reza A.; Bayanolhagh, Saeed; Taj, Leila; Ahmadi, Niloofar Eghbal; Abedinzadeh, Negin; Vakili, Farzaneh; Ahmadi, Ghazaleh; Mohraz, Minoo (Infectious Disorders - Drug Targets, 2018)
Background: Determination of the drug-resistant mutations has a crucial role in the management of HIV-1 infected patients. Objective: The aim of the current study was to evaluate drug resistance profile of Reverse transcriptase and Proteasegenes, and to find the correlation between drug resistance mutations and ART regimen to intensify physicians' options for the most effective therapy which could also influence the establishment of health-related policies at the national level in Iran. Method: HIV-1 RNA of 34 samples was extracted from plasma and RT Nested- PCR was performed and the final products were sequenced. Stanford HIV drug resistance sequence database was used for interpretation of the data. Results: In 14 patients out of 15, the following mutations were observed; Nucleoside RT Inhibitor (NRTI)-Resistance Mutations with the prevalence of 11 patients having this mutation at codon 184 (73%) and Non-Nucleoside RT Inhibitor (NNRTI)-Resistance Mutations with the prevalence of 8 patients having NNRTI mutations at codon 103(53%).In 17 patients, major Protease Inhibitor (PI) Resistance Mutations were found out in 2 (12%) of them while the minor PI was found in7 (41%) patients. Conclusion: An antiretroviral treatment consisting of nucleoside reverse transcriptase inhibitor, non-nucleoside reverse transcriptase inhibitor and protease inhibitor, impairs the emergence of a resistant strain and descends its prevalence among the community. Having a high rate mutation in participants of this study raises concerns about treatment failure in HIV infected people in Iran. Observing high mutations rates in participants of this study raises concerns about treatment failure in HIV infected people in Iran.
Keywords: HIV-1